Oncogenic Roles of Small Nucleolar RNA Host Gene 7 (SNHG7) Long Noncoding RNA in Human Cancers and Potentials - Najafi, Sajad; Ghafouri-Fard, Soudeh; Hussen, Bashdar Mahmud; Jamal, Hazha Hadayat; Taheri, Mohammad; Hallajnejad, Mohammad (Frontiers in Cell and Developmental Biology, 2022)
Long noncoding RNAs (lncRNAs) are a class of noncoding transcripts characterized with more than 200 nucleotides of length. Unlike their names, some short open reading frames are recognized for them encoding small proteins. LncRNAs are found to play regulatory roles in essential cellular processes such as cell growth and apoptosis. Therefore, an increasing number of lncRNAs are identified with dysregulation in a wide variety of human cancers. SNHG7 is an lncRNA with upregulation in cancer cells and tissues. It is frequently reported with potency of promoting malignant cell behaviors in vitro and in vivo. Like oncogenic/tumor suppressor lncRNAs, SNHG7 is found to exert its tumorigenic functions through interaction with other biological substances. These include sponging target miRNAs (various numbers are identified), regulation of several signaling pathways, transcription factors, and effector proteins. Importantly, clinical studies demonstrate association between high SNHG7 expression and clinicopathological features in cancerous patients, worse prognosis, and enhanced chemoresistance. In this review, we summarize recent studies in three eras of cell, animal, and human experiments to bold the prognostic, diagnostic, and therapeutic potentials.